Endividamento das famílias no estado do Amazonas no período da pandemia da Covid-19 - Souza, Augusto Henrique Doce (Brasil, 2024)
The COVID-19 pandemic had a significant socio-economic impact on the state of Amazonas, affecting the daily lives of consumers and their debt and default conditions. The general objective of this study was to understand consumer indebtedness and default during the COVID-19 pandemic in the state of Amazonas from 2020 to 2022, with specific objectives being to describe the degree of family indebtedness during this period, verify overdue bills of Amazonian consumers, and explain the reasons why families are unable to pay their debts. The justification for this study stems from the importance of observing the impact of the COVID-19 pandemic on indebtedness and default. The methodology used was descriptive, bibliographical, quantitative, and qualitative in nature, analyzing historical context and recent data related to indebtedness. The results and discussions addressed the degree of indebtedness, overdue bills, and default among Amazonians based on data from the National Survey of Consumer Indebtedness and Default (PEIC). Thus, it is concluded that the COVID- 19 pandemic altered the daily lives of Amazonian families, contributing to increased indebtedness and default. The findings indicate that the COVID-19 pandemic exacerbated family indebtedness, while increased interest rates and inflation heightened default rates among Amazonian families, exacerbating the trade-off between bills and basic expenses. Thus, it is concluded that the COVID-19 pandemic altered the daily lives of Amazonian families, contributing to increased indebtedness and default.